Rekonstruksi Pemikiran Pendidikan Islam - Suripto (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2014)
Islam as a source of reference values have been offered a grand design for the development of all areas of science including the science of Islamic education. However, in the plains of praxis, the grand design of science is actually eliminated by a scientific ideology of the Muslim community itself which is used to maintain the semantic falsehood epistimologi in the development of Islamic scholarship. So the building of knowledge in Islamic educational thought often prepared on the basis of the less obvious and less functional. Through a philosophical approach to the author asserts that the reconstruction of an ideal Islamic educational thought should put philosophy as the entry point and the basic paradigm for the entire building science.